Investigation of neuromodulation of the endbulb of Held synapse in the cochlear nucleus by serotonin and norepinephrine - Groshkova, Maria; Alvanos, Theocharis; Qi, Yumeng; Wang, Fangfang; Wichmann, Carolin; Hua, Yunfeng; Moser, Tobias (Frontiers in Cellular Neuroscience, 2025)
IntroductionSynapses vary greatly in synaptic strength and plasticity, even within the same circuitry or set of pre- and postsynaptic neurons. Neuromodulation is a candidate mechanism to explain some of this variability. Neuromodulators such as monoamines can differentially regulate presynaptic function and neuronal excitability. Variability is found also for the large calyceal synapses of the auditory pathway that display high synaptic vesicle (SV) release probability (Pvr) and large postsynaptic currents in vitro enabling reliable and temporally precise transmission of auditory information. In this study, we investigated whether the endbulb of Held synapse formed by auditory nerve fibers onto bushy cells (BCs) in the anteroventral cochlear nucleus (AVCN) of mice is modulated by norepinephrine (NE) and serotonin (5-HT).MethodsWe used electron microscopy (EM) of the cochlear nucleus (CN) to investigate the presence of monoaminergic projections. Furthermore, we performed immunohistochemistry to study the localization of monoamine transporters and receptors in the AVCN. We performed patch-clamp recordings from BCs to study spontaneous and evoked synaptic transmission as well as short-term plasticity of the endbulb of Held synapse and to investigate the excitability of the BCs.ResultsWe found EM evidence for putative monoaminergic varicosities in both ventral and dorsal divisions of the CN. Immunostaining for vesicular 5-HT and NE transporters revealed NE-containing and 5-HT-containing varicosities in the AVCN, juxtaposed to both endbulbs and BCs. Furthermore, we detected immunofluorescence for 5-HT1B, 5-HT4, and 5-HT7 receptors (R) and α2C-adrenergic receptors (AR) in BCs. Patch-clamp recordings from BCs revealed an increase in frequency of miniature excitatory postsynaptic currents (mEPSCs) upon application of NE but not 5-HT. Evoked synaptic transmission was unaffected by the application of either NE or 5-HT. Similarly, when studying the biophysical properties of the BCs, we did not observe effects of NE or 5-HT on low-voltage-activated K+ (KLVA+) and hyperpolarization-activated mixed cation (HCN) channels during application.DiscussionIn summary, we report evidence for the presence of monoaminergic innervation in the cochlear nucleus and for subtle functional NE-neuromodulation at the endbulb of Held synapse.